2022
DOI: 10.1002/ldr.4471
|View full text |Cite
|
Sign up to set email alerts
|

Allocation and transfer of photosynthetic 13C in the vegetation‐soil system and its response to permafrost degradation

Abstract: The Xing'an Mountains, located on the southern edge of the Eurasian permafrost zone, are sensitive to permafrost degradation. In particular, the impact of wetland degradation in permafrost regions on carbon sequestration capacity cannot be ignored. Therefore, there is an urgent need to understand the allocation and transfer of photosynthetic 13 C in the wetland vegetation-soil system and its response to permafrost degradation. Three regions with different types of permafrost were selected predominantly continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In agreement, the results showed that soil bacteria-to-fungi ratio was significantly and negatively correlated with SOC (R = −0.680; P < 0.05). Previous studies have found that plants channel up to 60 % of photosynthetically-derived C to the root system, including tissues, mucilage, or the exudation of organic compounds [ 35 , 36 ]. It can be mainly metabolized by soil fungi rather than bacteria, as fungi have a high ability in assimilating plant derived C, which results in the formation of more complex C compounds with lower degradability [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, the results showed that soil bacteria-to-fungi ratio was significantly and negatively correlated with SOC (R = −0.680; P < 0.05). Previous studies have found that plants channel up to 60 % of photosynthetically-derived C to the root system, including tissues, mucilage, or the exudation of organic compounds [ 35 , 36 ]. It can be mainly metabolized by soil fungi rather than bacteria, as fungi have a high ability in assimilating plant derived C, which results in the formation of more complex C compounds with lower degradability [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%